Cytotoxicity of triterpenes from the leaves of Garcinia prainiana King (Guttiferae) - On, Shamsul; Wan Salleh, Wan Mohd Nuzul Hakimi; Ahmad, Farediah; Sirat, Hasnah M; Bakhtiar, M. Taher (Marmara University, 2017)
Phytochemical investigation of the leaves of Garcinia prainiana resulted in the isolation of five triterpenes identified as squalene 1, friedelin 2, lupeol 3, 3β-hydroxyeupha-5,22-diene 4, and 3β-acetoxyeupha-5,22-diene 5. The structures of these compounds were established by analysis of their spectroscopic data, as compared to that of reported compounds. All compounds were tested for cytotoxicity against H1299 and A549 lung cancer cell lines using MTT assay. 3β-Acetoxyeupha-5,22-diene 5 exhibited the most significant activity against human non-small cell lung carcinoma cell lines, H1299 and A549 with IC50 values 18.0 μg/ml and 36.3 μg/ml, respectively.